Detecting Boosting Weak Signal via A Meminductive Multistable Chaotic System - Kang, Baolin; Qin, Wenjie (Frontiers in Physics, 2022)
In this paper, we rebuild a new meminductive chaotic circuit model based on Wien-bridge oscillator. Due to extremely multistability of the meminductive system, it can produce the phenomenon of infinitely many coexisting attractors. Such systems that spontaneously produce coexisting oscillations are relatively rare in the study of meminductive circuit system, and it is well suited as a pseudo-random number generator (PRNG). Then, a new weak signal detection model is established based on the proposed meminductive system. And this detection model can detect boosting weak signals with different amplitudes. The trajectory of objects can be predicted effectively by the boosting line spectrum in frequency domain. The experimental result shows the feasibility that the meminductive multistable system is applied in detection field.